Consider the equation above. Which of the following pairs show the correct values of ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let's consider p(x)= 2x^4 - 11x^3 + 16x^2 - 11x + 2 = 0. Then x=0 isn't a root of p(x). This implies that we can divide for x^2;
2x^2 - 11x + 16 - 11/x + 2/x^2 = 0;
2(x^2 + 1/x^2) - 11(x + 1/x) + 16 = 0;
2((x + 1/x)^2 - 2) - 11(x + 1/x) + 16 = 0; Now, we call y = x + 1/x. Therefore,
2(y^2 -2) - 11y + 16 = 0;
2y^2 - 11y + 14 = 0;
y = x + 1/x = 3/2 or 8